2019
DOI: 10.1039/c8na00093j
|View full text |Cite
|
Sign up to set email alerts
|

Jolly green MOF: confinement and photoactivation of photosystem I in a metal–organic framework

Abstract: Photosystem I (PSI) is a ∼1000 kDa transmembrane protein that enables photoactivated charge separation with ∼1 V driving potential and ∼100% quantum efficiency during the photosynthetic process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 76 publications
0
28
0
Order By: Relevance
“…1,2 In comparison to traditional porous solids such as activated carbon, mesoporous silica, and zeolites, MOFs have diverse topology structures, high surface area, ultrahigh porosity, and multiple tunable functions. [3][4][5] Therefore, it can be used in a wide range of applications, such as adsorption/separation, 6,7 photoelectronics, 8,9 energy conversion, 10,11 drug delivery, 12 chemical sensing, 13 and catalysis. 14 Actually, the size and shape of pores within MOFs are one of decisive parameters for the above-mentioned applications, since the guest species accessing or leaving the internal active sites of MOFs is a prerequisite for the proceeding of reaction.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 In comparison to traditional porous solids such as activated carbon, mesoporous silica, and zeolites, MOFs have diverse topology structures, high surface area, ultrahigh porosity, and multiple tunable functions. [3][4][5] Therefore, it can be used in a wide range of applications, such as adsorption/separation, 6,7 photoelectronics, 8,9 energy conversion, 10,11 drug delivery, 12 chemical sensing, 13 and catalysis. 14 Actually, the size and shape of pores within MOFs are one of decisive parameters for the above-mentioned applications, since the guest species accessing or leaving the internal active sites of MOFs is a prerequisite for the proceeding of reaction.…”
Section: Introductionmentioning
confidence: 99%
“…Several previous works reported the application of PSI in an extracellular environment coupled with artificial devices, 15,16,2022,24 carbon nanotubes, 56 metal oxide nanowires, 57 plasmonic nanostructures, 3436 conductive polymers, 58 redox hydrogel, 18,59 or assembled in metal–organic framework. 32 The advantage of the technology herein proposed, in addition to the increased photochemical activity and increased stability of PSI, consists of the organic matrix used for PSI encapsulation: PLGA polymers are environmental friendly compounds since they are biocompatible, 41,43 and their ester linkages are rapidly hydrolyzed once they enter a cell to produce the monomers, lactic acid and glycolic acid, which are then easily metabolized via the Krebs cycle. PLGA-based MPs have been indeed approved by U.S. Food and Drug Administration (FDA) and by the European Medicine Agency (EMA) 41 as a delivery vehicle for drugs, proteins, and other molecules such as DNA, RNA, and peptides.…”
Section: Discussionmentioning
confidence: 99%
“…The LIBS experimental set-up and procedure have been described in detail elsewhere for PSI@ZIF-8 as well as for diverse biological and nanomaterial compositions. 42,[50][51][52][53][54][55] Raman experiments were performed on a confocal Raman spectrometer (Witec Alpha 300), with a laser wavelength of 532 nm, an objective of 20Â, a grating with 600 grooves per mm, a numerical aperture (NA) of 0.42, and a local power of 600 mW. The laser spot size was estimated to be 1 mm.…”
Section: Libs and Raman Analysis Of Psi@zif-8 Compositionmentioning
confidence: 99%
“…Specically, certain organic complexes have high enough electronic conductivities to be considered fully organic metals, such as the well-known TTF-TCNQ salt. 41 Herein, inspired by our successful encapsulation of PSI in ZIF-8 (PSI@ZIF-8) 42 we report the use of PSI@ZIF-8 composites as starting scaffolding materials to drive the constituent cations (namely, Zn 2+ or the imidazole ion, H 2 mim + ) from ZIF-8 towards subsequent formation of charge transfer complexes with TCNQ. While it has recently been demonstrated that a copper-based MOF can undergo ligand substitution to form CuTCNQ, 43 our work enables a transformation in an aqueous environment amenable to a host of biological materials rather than an organic solvent-a heretofore unachievable task.…”
Section: Introductionmentioning
confidence: 99%